Library Workers’ Perceptions of Immigrant Acculturation: Renewed Understandings for Changing Contexts - Ndumu, Ana; Park, Hayley; Siebold, Connie (Evidence Based Library and Information Practice, 2025)
Objective – Immigrants’ adjustment to U.S. society, also known as immigrant acculturation, is a vast area of study, but there are few studies relating to immigrant acculturation within the library and information science field. Methods – Data from 131 survey responses and 20 interviews suggest that library workers are somewhat familiar with the immigrant acculturation process, but specific and evidence based training can further their knowledge. Results – Insight on immigrant acculturation contextualizes immigrants’ realities and thus assists library workers in being aware of and responsive to the nuances of adjusting to and thriving in a new country like the U.S. Conclusion – In the face of anti-immigration legislation and heightened xenophobic misinformation, librarians need professional development drawn from empirical investigations of immigrants’ acculturative experiences.